Adjunctive Use of Bioactive Iron Citrate (Synthesit®) for Mitigating Chemotherapy-Induced Myelosuppression and Hepatotoxicity in Advanced Tongue Squamous Cell Carcinoma: A Case Report - Angela, Rusnac; Baig, Shahbaz (Futurity Medicine, 2025)
Intoduction: Cancer of the tongue with regional lymph node metastasis often requires aggressive chemotherapeutic regimens that may lead to severe haematological toxicity and treatment interruptions. Supportive therapies, including Synthesit®, a bioactive iron-based supplement, may help sustain treatment tolerance. Case Presentation: This case report describes a 47-year-old patient with stage III cancer of the tongue root receiving CF (cisplatin + 5-fluorouracil) chemotherapy. After the first cycle, the patient developed profound anaemia, leukopenia, thrombocytopenia, and hepatotoxicity, necessitating treatment suspension. Supportive therapy with Synthesit®, Sorbifer, and hepatoprotectors was initiated. Within two weeks, haematological and hepatic parameters improved sufficiently to resume chemotherapy. The aim was to evaluate Synthesit® as an adjunctive agent, focusing on hematopoietic recovery, hepatoprotection, and tolerance to chemotherapy and radiotherapy. A single-case study design using electronic medical records, chemotherapy logs, laboratory test results, and imaging was employed. Hematologic and hepatic biomarkers were tracked across CF chemotherapy, Synthesit® administration, paclitaxel treatment, and subsequent radiotherapy. Following the initial CF cycle, severe myelosuppression occurred (hemoglobin 65 g/dL, WBC 3.5×10³/µL, platelets 120×10³/µL) along with hepatotoxicity (ALT 50 U/L, AST 76 U/L). After two weeks of Synthesit®, Sorbifer, and hepatoprotectors, hematologic values recovered to >90% of baseline, and liver enzymes nearly normalised. Chemotherapy was resumed, and four additional CF cycles were completed without recurrent grade 3-4 toxicities. Haemoglobin increased from 10.5 to 13.1 g/dL, RBC and hematocrit improved, and platelets stabilised. During metronomic paclitaxel plus Synthesit®, blood counts remained stable, enabling completion of 42 Gy radiotherapy. Follow-up MRI confirmed disease stability. Conclusion: This case suggests Synthesit®, combined with hepatoprotective therapy and iron supplementation, may support hematologic recovery and facilitate continuation of cancer treatment.